EDUCATION IN DIVERSITY: REFLECTIONS ON TEACHER TRAINING AND PEDAGOGICAL PRACTICE IN THE PROPOSAL OF INCLUSIVE EDUCATION - Eduarda dos Santos, Maria (Revista Gênero e Interdisciplinaridade, 2024)
Introduction: Students with special educational needs are included in the perspective of inclusive education, which, in recent years, has gained prominence and has been widely discussed Objective: to carry out a survey of some works from the last 6 years that cover the theme of Education and teaching pedagogical practice in the proposal for inclusive education Methodology: This is a descriptive literature review with qualitative characteristics in the Scielo and Google Scholar databases in articles published, in Portuguese, between 2015 and 2021. Conclusions: It is possible to conclude Although educating in diversity is possible, as long as public policies are actually implemented, teacher training requires more investment and attention from schools.